2017
DOI: 10.3389/fpsyg.2017.01562
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of Inhibition of Return: Evidence from Steady-State Visual Evoked Potentials

Abstract: Inhibition of return (IOR) refers to slower responses to targets at a previously cued location than that at an uncued location. The time course of IOR has long been a topic of interest in the field. Investigations into the time course of IOR are typically performed by examining the magnitude of IOR under various cue-target onset asynchrony (CTOA) conditions. Therefore, the results are vulnerable to influence of factors that could affect the target processes (e.g., the frequency of the target type). In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
1
7
1
Order By: Relevance
“…However, the IOR-modulated SSVEP effect observed in Li et al (2017) should have been present at both 8 and 20 Hz, not only at 20 Hz, because it has been demonstrated that although SSVEPs are present in the 12-25 Hz and 25-50 Hz ranges (Herrmann, 2001), they are strongest in the alpha range (approximately 8-12 Hz; Herrmann, 2001;Pastor, Artieda, Arbizu, Valencia, & Masdeu, 2003), with maximal responses at about 10 Hz for luminance flickers (Fawcett, Barnes, Hillebrand, & Singh, 2004;Regan, 1966;Srinivasan et al, 2006). The absence of SSVEP modulation at their 8 Hz frequency could potentially be due to the eye movements of participants not being monitored by means of an eye-tracker during the task, which has been found to be a serious confounding factor that could lead to inconsistent IOR results (Chica, Klein, Rafal, & Hopfinger, 2010a;Rafal et al, 1989).…”
Section: Ior and Ssvepsmentioning
confidence: 90%
See 3 more Smart Citations
“…However, the IOR-modulated SSVEP effect observed in Li et al (2017) should have been present at both 8 and 20 Hz, not only at 20 Hz, because it has been demonstrated that although SSVEPs are present in the 12-25 Hz and 25-50 Hz ranges (Herrmann, 2001), they are strongest in the alpha range (approximately 8-12 Hz; Herrmann, 2001;Pastor, Artieda, Arbizu, Valencia, & Masdeu, 2003), with maximal responses at about 10 Hz for luminance flickers (Fawcett, Barnes, Hillebrand, & Singh, 2004;Regan, 1966;Srinivasan et al, 2006). The absence of SSVEP modulation at their 8 Hz frequency could potentially be due to the eye movements of participants not being monitored by means of an eye-tracker during the task, which has been found to be a serious confounding factor that could lead to inconsistent IOR results (Chica, Klein, Rafal, & Hopfinger, 2010a;Rafal et al, 1989).…”
Section: Ior and Ssvepsmentioning
confidence: 90%
“…As an alternative to ERPs, steady-state visual evoked potentials (SSVEPs) are commonly used to investigate visual information processing (Regan, 1968) and allow for attention to be measured continuously (Morgan, Hansen, Hillyard, & Posner, 1996). Compared with ERPs, SSVEPs are easier to quantify (Luck, 2014) and less prone to artifacts (Regan, 1989), making them a valuable tool for measuring attention in paradigms, such as the spatial cueing task (Li et al, 2017).…”
Section: Steady-state Visual Evoked Potentialsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have demonstrated that these SSVEP signals are modulated by spatial attention (i.e., the signal is enhanced when attended), e.g., [51,52]. As far as we know, only one study [53] has employed this technique to explore the sensory consequences of an uninformative peripheral cue. This study found a biphasic pattern with enhanced signals from the cued location immediately after the appearance of the cue reversing to suppressed signals beginning about 200 ms later.…”
Section: Human Brain Imagingmentioning
confidence: 99%